Brokerage as an institutional strategy in fragmented fields: the crafting of social entrepreneurship - Collavo, T (2018)
Although the scholarship on organizational fields has prevalently focused on emerging, mature and disrupted fields, some social arenas cannot be classified in any of these categories. One such field is that of social entrepreneurship. Despite its progressive establishment and the development of shared norms, understandings, regulations and values governing all of its players, this field still presents unclear boundaries, multiple conceptions, and a high ambiguity in terms of legitimate roles, practices and organizational forms. How can this be the case? The work of some scholars shows that meso-level factors are required to explain the peculiarity of this field. This study builds on their findings and uses the social entrepreneurship field in England as setting to explore how institutional agents can favour the creation of a fragmented field and successfully operate in it. Influencing a fragmented field requires both the creation and the maintenance of a coalition of key stakeholders supporting the enactment of the desired institutional architecture over time. Therefore, this research explores what organizations do to maintain the support of multiple stakeholders in competitive settings and to use the advantages that this creates for sustaining the co-existence of their desired field’s conception and institutional architecture with competing ones. Given the advantages that brokers have in such settings and in pursuing such a strategy, this work makes use of the well-developed literature on brokerage strategies, which focuses on tertius gaudens and tertius iungens strategic orientations, and connects it with that on institutional agency. By using as case studies four brokering agencies active in the social entrepreneurship field in England, this study discovers that combinations of gaudens and iungens strategic orientations, when used by institutional agents, can help them create and sustain over time their sub-field in face of competition. Furthermore, it explores how the co-existence of multiple organizations adopting complementary brokerage strategies as institutional ones, can lead to the creation of a permanently fragmented field. Together, these findings contribute to develop the literature on brokerage, on institutional agency — especially in relation to fragmented fields —, and that on social entrepreneurship.